Pressure-induced phase transitions of KTiOAsO4 by Raman spectroscopy - Shen, Z. X. (2018)
Potassium titanyl orthoarsenate KTiOAsO4 has been studied by Raman spectroscopy up to 16 GPa. Three first-order pressure-induced phase transitions are inferred from Raman data. The first phase transition takes place at 3. 2 GPa, as indicated by drastic spectral changes in all the internal modes of the TiO6 octahedra. The second phase transition occurs at 7. 5 GPa with striking spectral changes in the high wavenumber region for Raman modes involving both TiO6 and AsO4 groups. Several modes belonging to TiO6 also soften between 0-7. 5 GPa. The third phase transition occurs near 10 GPa and the high-pressure phase should be of higher symmetry.